DESCRIPTION OF HYPERTENSION LEVELS IN PRIMARY HYPERTENSION ADULTS AND ELDERLY IN KARANGBINANGUN LAMONGAN DISTRICT - Iswatun, Iswatun; Wijayanti, Endah Sri; Fadliyah, Lailatul; Purwanto, Cucuk Rahmadi; Rohmawati, Iin (Universitas Airlangga, 2021)
Introduction: Hypertension is often a silent killer because it is often without symptoms that warn of a problem. Symptoms that appear are often considered as common disorders, so that the victim is too late to realize that the disease is coming. Hypertension is an increase in blood pressure above normal limits with systolic value of 140 mmHg and diastolic value of 90 mmHg. The purpose of this study was to determine the level of hypertension in patients with primary hypertension in Karangbinangun Lamongan District. Method: This research design using descriptive with a population of 70 respondents then sampled using simple random sampling and get a sample of 64 respondents, in accordance with the inclusion criteria, are healthy patients and willing to sign the informed consent The variable in this study is the level of hypertension. The data of this study were taken from the results of blood pressure measurements by standards WHO. The data is tabulated in the form of frequency distribution by categorizing hypertension into mild, moderate and severe. Result: The results showed that half of the respondents (50%) had mild hypertension, 28.1% moderate hypertension and 21.9% severe hypertension. Conclusion: Seeing the results of this study, that there are still many people who have hypertension, so health education by health workers and family is needed to prevent recurrence.